Modelling of Thin Structural Polymer Composites for Use of Automobiles -Review- - Daisuke Narita; Yoshihiro Narita (EPI International Journal of Engineering, 2018)
This review article introduces first a number of previous works and commercial examples on the use of fiber-reinforced polymer materials in the application to automobile structural components, and secondly considers the modeling for thin components of fiber-reinforced polymer composites with emphasis on the roofs and fenders of the automobiles. The need of this study seems obvious, since particularly in the sportive and high-grade automobiles, the composite materials have already replaced conventional metal materials resulting in the significant reduction of structural weight. In such application, laminated composite panels (shallow shells) are used for models of automotive panels. The structural components in the automobile are extensively exposed to vibration excitation and other external disturbances in practical use, and resonance phenomenon may cause disturbing effects such as noise and fatigue. One countermeasure for such negative effects is to make use of tailoring advantages for fiber reinforced laminated composites and the feasibility for optimization process is suggested.